ANALISIS PERBANDINGAN NET PROFIT MARGIN (NPM) PADA PT UNILEVER INDONESIA,TBK DENGAN PT INDOFOOD SUKSES MAKMUR,TBK - NASYIRATUNNISA, NASYIRATUNNISA; MUNIARTY, PUJI (GANEC SWARA, 2024)
This study aims to determine the differences in using the Net Profit Margin (NPM) ratio between PT Indofood Sukses Makmur Tbk and PT Unilever Indonesia Tbk. This research is quantitative. The research instruments used in this study include a literature review of previous research and financial reporting data documents from PT Unilever Indonesia, Tbk and PT Indofood Sukses Makmur, Tbk over ten years between 2013–2022. Data collection techniques involve literature review and documentation. Data analysis techniques include Net Profit Margin (NPM) Analysis and Normality Test and independen sampel test. The population and sample comprise the financial statements of PT Unilever Indonesia Tbk from 2010 to 2022 and the performance of PT Indofood Sukses Makmur Tbk over the same 13-year period. The research results obtained from the demo show that 20% is below the standard, consistent with the average net profit margin (NPM). If the net profit margin is less than the industry standard of 20%, it indicates that the company does not have good financial performance or has not managed to allocate sufficient profit to fund the property. With variations from year to year, a higher NPM indicates better company performance as it can cover the costs of raw materials needed for business operations. However, the t-test shows that there is no difference between PT Unilever Indonesia Tbk and PT Indofood Sukses Makmur Tbk